Experiences of breastfeeding support at work: A qualitative study among clothing factory workers in South Africa - Botha, Gina (University of Cape Town, 2020)
South Africa had the lowest exclusive breastfeeding rates in the world in 2012 at 8%. This increased to 32% in 2016 but the progress is still slow. Return to work is one of the main reasons working women stop breastfeeding. A descriptive qualitative research design was used to guide this study, which explored support for workplace breastfeeding. This study focused on a vulnerable group of low-income women working in clothing factories in Cape Town, a female dominated industry in South Africa. The research aimed to develop an improved understanding of breastfeeding support at work for these women. Given South Africa's legacy of colonialism and apartheid, these women are mainly black and poor. High poverty rates in this context often mean that they return to work soon after childbirth because of economic necessity, placing further constraints on breastfeeding. The study's findings confirm that despite legislated maternity protection and breastfeeding breaks, the enforcement of these laws is very low. In investigating the ways low-skilled, low paid women in clothing factories navigate this situation, four key themes emerged: 1) their workplaces are designed for men and machines; 2) they receive limited workplace breastfeeding support; 3) there is a lack of communication and transparency about breastfeeding at work and 4) their social and economic context plays a role in their ability to breastfeed at work. With these findings, low-cost recommendations for improving workplace support for breastfeeding are presented.